Development of phantom materials with independently adjustable CT- and MR-contrast at 0.35, 1.5 and 3 T. (2nd February 2021) - Elter, A; Hellwich, E; Dorsch, S; Schäfer, M; Runz, A; Klüter, S; Ackermann, B; Brons, S; Karger, C P; Mann, P
Abstract: Quality assurance in magnetic resonance (MR)-guided radiotherapy lacks anthropomorphic phantoms that represent tissue-equivalent imaging contrast in both computed tomography (CT) and MR imaging. In this study, we developed phantom materials with individually adjustable CT value as well as T 1 - and T 2 -relaxation times in MR imaging at three different magnetic field strengths. Additionally, their experimental stopping power ratio (SPR) for carbon ions was compared with predictions based on single- and dual-energy CT. Ni-DTPA doped agarose gels were used for individual adjustment of T 1 and T 2 at 0.35, 1.5 and 3.0 T. The CT value was varied by adding potassium chloride (KCl). By multiple linear regression, equations for the determination of agarose, Ni-DTPA and KCl concentrations for given T 1, T 2 and CT values were derived and employed to produce nine specific soft tissue samples. Experimental T 1, T 2 and CT values of these soft tissue samples were compared with predictions and additionally, carbon ion SPR obtained by range measurements were compared with predictions based on single- and dual-energy CT. The measured CT value, T 1 and T 2 of the produced soft tissue samples agreed very well with predictions based on the derived equations with mean deviations of less than 3.5 % . While single-energy CT overestimates the measured SPR of the soft tissue samples, the dual-energy CT-based predictions showed a mean SPR deviation of only 0.2 ± 0.3 % . To conclude, anthropomorphic phantom materials with independently adjustable CT values as well as T 1 and T 2 relaxation times at three different magnetic field strengths were developed. The derived equations describe the material specific relaxation times and the CT value in dependence on agarose, Ni-DTPA and KCl concentrations as well as the chemical composition of the materials based on given T 1, T 2 and CT value. Dual-energy CT allows accurate prediction of the carbon ion range in these materials.